Perubahan nilai kedaulatan pangan pada sistem pertanian subak di Bali dengan pendekatan life story - Fauzan, Riantama Sulthana; Sugiharti, Endang (Institute for Advanced Science, Social, and Sustainable Future, 2024)
As a local wisdom agricultural system in Bali, Subak is threatened in maintaining food sovereignty in the Bali region. This is because farmers no longer fully implement the Tri Hita Karana principles in their agricultural systems. Currently, farmers are turning to the Green Revolution agricultural system which has principles that are contrary to those contained in the food sovereignty system. This study aims to determine the extent to which the Green Revolution has degraded the food sovereignty of Subak which applies the values of Tri Hita Karana so that it can identify the root causes of problems and solutions that can be carried out to maintain food sovereignty. This research uses qualitative research design and Life History method to understand various changes that occur in depth. Data collection is done using observation, literature, and conduct direct interviews with three Subaks in Tabanan regency. The results showed a shifting orientation from the human-based agricultural system to capital and technology. The results of this shift degrade the food sovereignty of Subak, especially the rights of farmers as well as environmental and cultural degradation. The Green Revolution did not directly affect Subak's food sovereignty, but the farmers who were influenced by changes brought by the Green Revolution made Subak not sovereign.